A conceptual model of fertility concerns among adolescents and young adults with cancer. Issue 8 (17th April 2021) - Canzona, Mollie R.; Victorson, David E.; Murphy, Karly; Clayman, Marla L.; Patel, Bonnie; Puccinelli‐Ortega, Nicole; McLean, Thomas W.; Harry, Onengiya; Little‐Greene, Denisha; Salsman, John M.
Abstract: Objective: For adolescents and young adults (AYAs), cancer‐related fertility concerns (FC) are salient, disruptive, and complex. Clinical communication about FC and fertility preservation options are suboptimal, increasing patient distress. The purpose of this study is to construct a conceptual model of FC among AYAs with cancer to inform future measurement development. Methods: Concept elicitation interviews were conducted with a purposive sample of stakeholders: 36 AYAs (10 adolescents, 12 emerging adults, and 14 young adults), 36 AYA oncology health care providers, and 12 content experts in cancer‐related infertility. The constant comparative method was used to identify themes and properties that illustrate AYAs' conceptualization and/or experience of FC. Results: Thirteen themes characterized FC among AYAs with cancer, varying by stakeholder group and domain affiliations. Themes were grouped by four domains (e.g., affective, information, coping, and logistical), which organized the conceptual model. Affective experiences were further determined to be an important component within the other three domains. AYAs' fertility and fertility preservation experiences were shaped by communication factors and timing factors including placement along the lifespan/cancer continuum. Conclusions: AYA FC are characterized by uncertainty and confusion that may contribute to future decisional regret or magnify feelings of loss. Results add to previous research by examining individual, relational, and health care factors that fluctuate to inform fertility preservation perceptions and decision‐making across the AYA age spectrum. Findings will be used to develop and test new self‐report measures of FC among AYAs with cancer and survivors using classic and modern measurement theory approaches.